Synthesis of g-C3N4/NiO-carbon microsphere composites for Co-reduction of CO2 by photocatalytic hydrogen production from water decomposition. (10th July 2022) - Sun, Meng; Zhou, Yunlong; Yu, Teng
Abstract: In this paper, a g-C3 N4 /NiO/corn straw derivative carbon microsphere composite photocatalyst was successfully prepared. Photoelectric studies show that a heterojunction was formed between g-C3 N4 and NiO nanosheets, and the graphitized carbon microspheres were successfully modified on g-C3 N4 and NiO nanosheets. The heterostructure between g-C3 N4 and NiO works synergistically with the conductivity of carbon microsphere, resulting in H2 production and CO2 reduction in photocatalysis. Photocatalytic experiments show that the photocatalytic performance of g-C3 N4 /NiO/carbon microsphere composite is enhanced, and the highest H2 production rate was 36–58 times higher than that of pure g-C3 N4 . In the presence of CO2 gas, H2 production and CO2 reduction occur simultaneously. The possible mechanism of H2 production combined with CO2 reduction photocatalysis is analyzed from the perspective of thermodynamics and kinetics. The g-C3 N4 /NiO/carbon microsphere composite has a stronger H2 evolution performance than CO2 reduction performance. The change in free energy (ΔG) for the conversion of CO* to free CO gas is 0.52 eV, and CO release is the key step affecting the synergistic reduction of CO2 by H2 . This study provides new strategies for the synergistic reduction of CO2 by photocatalytic technology for H2 production. Highlights: NiO/g–C3 N4 –carbon microsphere composites are successfully prepared. NiO/g–C3 N4 –carbon microsphere composites show co-reduction of CO2 by H2 production. The possible mechanism of co-reduction of CO2 by H2 production is analyzed. Carbon microspheres increase the electron transfer rate of the composite.